Reinvestigation of Derris reticulata - Hunsa Prawat (2018)
The novel compound 1‴-hydroxy-2‴,3‴-epoxylupinifolin (1), together with three known prenylated flavanones were identified from the stem of Derris reticulata during our reinvestigation of the plant. The structures were determined by spectroscopic methods including detailed study of NMR spectral data (DEPT, 2D-COSY, HMQC and HMBC) as well as by chemical derivatizations. copy; Swets & Zeitlinger.